Glass transition and stickiness characteristics of sea tangle powder fermented with Lactobacillus brevis. Issue 6 (7th May 2021) - Yu, Daeung; Kwon, Gicheol; An, Jihye; Kim, Hyo Jin; Chung, Donghwa
Abstract: Glass transition and stickiness characteristics of fresh and Lactobacillus brevis ‐fermented sea tangle powders, at different storage temperature and water activities ( a w ), were investigated. For both powders, glass transition temperature ( T g ) decreased from 75°C to −72°C with increasing a w from 0 to above 0.9. Sticky point temperature ( T s ) was higher than T g by about 13−22°C, and also decreased with increasing a w . Higher T g and T s values were measured for fermented powder, and for powders stored at higher temperatures. Microstructure analysis revealed water‐induced particle aggregation and caking at a w >0.43. A storage stability study found that fermented powder was more stable than a fresh one, and a low storage temperature was preferred due to reduced molecular mobility. When stored at 4°C, the fermented powder remained non‐sticky as long as the a w remained below 0.8 (or the moisture content was below 0.76 g/g dry matter). Practical applications: Sea tangle ( Saccharina japonica ) contains γ‐aminobutyric acid (GABA), a major inhibitory neurotransmitter having beneficial physiological effects, such as diuretic, hypotensive, and tranquilizing activities. Fermentation of sea tangle with Lactobacillus brevis can increase the amount of GABA by about 100 times. However, the use of fermented sea tangle powder is greatly limited because its moisture‐induced stickiness and glass‐to‐rubbery state transition by strong hygroscopic nature significantly reduce the stability, safety, and quality of the powder during handling, processing, storage, and distribution. The present study provides a useful guideline for the safe and effective use of fermented sea tangle powder by providing information essential for understanding the relationships among the moisture sorption, glass transition, and stickiness of the powder.